PENGARUH MODAL, STRUKTUR PERSAINGAN, DAN PENDAPATAN TERHADAP INDEKS DAYA SAING UMKM KOTA BATU - Munifatik Munifatik; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2018)
BSTRACTThis research was conducted with the aim of: 1) To determine thesimultaneous effect of capital, competition structure and income on the MSMECompetitiveness Index in Batu City. 2) To determine the effect of partial capital,Competition Structure and Income on the MSME Competitiveness Index in BatuCity.The population in this study is all MSME’s in Indonesia. The samplingmethod in this study is purposive sampling method. So that obtained a sampleof 43 MSME in Batu City. The analytical method used in this study is multiplelinear regression.The results of the study show that: 1) Simultaneously Capital,Competition Structure, and Revenue significantly influence the CompetitivenessIndex. 2) Partially Capital does not significantly influence the CompetitivenessIndex. 3) Partially the Competition Structure has a significant positive effect onthe Competitiveness Index. 4) Partially Revenue has a significant positive effecton the Competitiveness Index.Keywords: Capital, Competition Structure, Income, MSME CompetitivenessIndex